2020
DOI: 10.2147/ceor.s265994
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analysis of the Health and Budgetary Impact of Chondroitin Sulfate Prescription in the Treatment of Knee Osteoarthritis Compared to NSAIDs and COXIBs</p>

Abstract: Background Chondroitin sulfate, alone or associated with glucosamine (CS), is an effective treatment of osteoarthritis, better tolerated than non-steroidal anti-inflammatory drugs (NSAIDs) and cyclooxygenase 2 inhibitors (COXIBs) at gastrointestinal, cardiovascular and renal levels. Objective To estimate the health impact (toxicity by NSAIDs/COXIBs avoided with CS with or without glucosamine) and economic impact (savings due to avoided toxicities) of treatment of knee o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(28 reference statements)
0
1
0
6
Order By: Relevance
“…Also, recently Rubbio-Teres showed that due to its better tolerability profile, chondroitin/glucosamine treatment is expected to prevent thousands of adverse events over the next three years and generate considerable savings for the national health system comparing with non-steroidal anti-inflammatory drugs and cyclooxygenase 2 inhibitors [21].…”
Section: Glucosamine/chondroitinmentioning
confidence: 99%
“…Also, recently Rubbio-Teres showed that due to its better tolerability profile, chondroitin/glucosamine treatment is expected to prevent thousands of adverse events over the next three years and generate considerable savings for the national health system comparing with non-steroidal anti-inflammatory drugs and cyclooxygenase 2 inhibitors [21].…”
Section: Glucosamine/chondroitinmentioning
confidence: 99%
“…Опубликованный недавно метаанализ 8 КИ показал высокую эффективность и безопасность препарата Хондрогард ® , который является фармацевтическим ХС [31]. Следует отметить, что основные ограничения, возникающие при назначении НПВП у лиц пожилого возраста, -кардиоваскулярный риск и хроническая болезнь почек -не препятствуют использованию ХС [32][33][34].…”
Section: рекомендации по планированию комплексных стратегий лечения хб у пациентов с гериатрическими синдромамиunclassified
“…О В P E М Е Н Н А Я Р Е В М А Т О Л О Г И Я № 6 ' 2 1 О Р И Г И Н А Л Ь Н Ы Е И С С Л Е Д О В А Н И Я / O R I G I N A L I N V E S T I G A T I O N S 30Современная ревматология. 2021;15(6):[26][27][28][29][30][31][32] …”
unclassified
“…Пациенты предпочитают препараты, обладающие минимальными побочными эффектами [44], что определяет использование ХС и ГЛ в качестве лекарственных средств первой линии для длительного лечения ОА при наличии коморбидных заболеваний. Применение неадекватных доз препаратов и лекарственных средств с неуточненным составом может привести к недостаточной эффективности, плохой приверженности терапии и неудовлетворенности пациента лечением [19,45]. Терафлекс содержит рекомендованные ESCEO дозы ГЛ и ХС -1500 и 1200 мг/сут соответственно.…”
unclassified
“…Комбинацию ХС и ГЛ рекомендовано использовать последовательно не менее 6 мес. Трехлетняя экономия при терапии SYSADOA по сравнению с НПВП с учетом возможных желудочно-кишечных и сердечно-сосудистых осложнений составила 21,8 млн евро [45].…”
unclassified